PELAKSANAAN PROGRAM PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SDN 20 MATARAM - Ketut Sri Kusuma Wardani; Ni Luh Putu Nina Sri Warthini; Aisa Nikmah Rahmatih; Fitri Puji Astria; Nurwahidah Nurwahidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to determine the implementation of inclusive education programs for children with special needs (ABK) in SDN 20 Mataram. This type of research in this study is qualitative research. Data collection techniques in research using interview techniques, observation, and documentation. This study uses data analysis techniques that are descriptive qualitative. The results showed that the implementation of inclusive education programs at SDN 20 Mataram used the 2013 curriculum, but for students with special needs who could not attend the material in regular classes, the special tutor made curriculum modifications according to the needs and abilities of students with special needs called the curriculum PPI (Individual Learning Program). The implementation of inclusive learning at SDN 20 Mataram is carried out with a regular class model where students with special needs learn together with other regular students, but in certain times students with special needs can be drawn into the inclusive resource space by special tutors, this is because seen from the condition of students with special needs who still cannot fully adapt to the abilities of their peers in regular classes.